Dante and Aquinas A Study of Nature and Grace in the Comedy - Took, John (Ubiquity Press, 2013)
Christopher Ryan's study of Dante and Aquinas, touching on issues of nature and grace, of explicit and implicit faith, and of desire and destiny, is intended to mark the difference between them in key areas of theological sensibility. Re-shaped and revised by John Took on the basis of papers made available to him from Christopher Ryan's estate, it seeks to deepen our understanding of one of the great cultural encounters in European letters. (DOI: 10.5334/bad)